2001
DOI: 10.1111/j.1151-2916.2001.tb00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength Degradation and Failure Mechanisms of Electron‐Beam Physical‐Vapor‐Deposited Thermal Barrier Coatings

Abstract: Failure mechanisms were determined for electron-beam physical-vapor-deposited thermal barrier coating (TBC) systems from the degradation of mechanical properties and microstructural changes in a furnace cycle test. Bond strength degradation for TBCs resulted from the initiation and growth of interfacial delamination defects between the yttriastabilized zirconia topcoat and the thermally grown alumina (TGO). It is proposed that defects started from concave depressions in the bondcoat surface created by the grit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…Prior observations Mumm and Evans, 2000;Mumm et al, 2001;Ruud et al, 2001;Rebello and Levi, 2002;Spitsberg et al, 2002;Wright and Evans, 1999) and simulations (He et al, 2000(He et al, , 2002Karlsson and Evans, 2001;Karlsson et al, 2002a, b) have suggested ve prerequisites for the instability. (a) The tempera ture must be cycled.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Prior observations Mumm and Evans, 2000;Mumm et al, 2001;Ruud et al, 2001;Rebello and Levi, 2002;Spitsberg et al, 2002;Wright and Evans, 1999) and simulations (He et al, 2000(He et al, , 2002Karlsson and Evans, 2001;Karlsson et al, 2002a, b) have suggested ve prerequisites for the instability. (a) The tempera ture must be cycled.…”
Section: Introductionmentioning
confidence: 92%
“…The simulations have revealed that the propagation of the instability depends on the interaction between three dierent strains: cyclic plasticity in the bond coat, growth in the TGO, and the thermal expansion mist between the TGO and the substrate. Moreover, the model demonstrates that the TBC layer provides constraint that inhibits the instability unless crack-like imperfections are present in the TBC (Karlsson et al, 2002;Ruud et al, 2001). While the model appears to duplicate the eects observed in the experiments, the interactions are suciently complex that the simulations have not been amenable to deconvolution of the inuences of the properties of the individual material constituents.…”
Section: Introductionmentioning
confidence: 99%
“…16) [20]. Given the existence of weak deposition planes in the TBC [15,17,43], this stress is sufficient to create cracks, which locally eliminate the constraint of the TBC, allowing the instability to propagate at a rate essentially the same as that absent in the TBC (Fig. 3).…”
Section: Layered Systemsmentioning
confidence: 99%
“…Several authors have proposed using the (apparent) interfacial fracture toughness to describe the damage accu mulation before spallation [4][5][6][7] and -if the fracture tough ness can be determined as a function of loading history -as a universal damage parameter in life prediction models [8]. Due to the complex structure of TBCs, establishing the interfacial fracture toughness is a highly challenging task, and an effective method for determining such a property has still not been established.…”
Section: Introductionmentioning
confidence: 99%